2006
DOI: 10.1104/pp.106.089169
|View full text |Cite
|
Sign up to set email alerts
|

Common Plantain. A Collection of Expressed Sequence Tags from Vascular Tissue and a Simple and Efficient Transformation Method

Abstract: The vascular tissue of higher plants consists of specialized cells that differ from all other cells with respect to their shape and size, their organellar composition, their extracellular matrix, the type of their plasmodesmata, and their physiological functions. Intact and pure vascular tissue can be isolated easily and rapidly from leaf blades of common plantain (Plantago major), a plant that has been used repeatedly for molecular studies of phloem transport. Here, we present a transcriptome analysis based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 64 publications
1
42
0
Order By: Relevance
“…In addition, RT-PCRs were performed with primers specific for PmSUC2 and for PmUBQ1 (ubiquitin 5 control). Macroarray analyses (data not shown) and PCR analyses (Pommerrenig et al, 2006) had demonstrated that PmUBQ1 expression is not influenced by salt treatment. The data presented in Figure 2A confirmed the salt-responsive induction for PmPLT1 and PmPLT2 expression shown in Figure 1.…”
Section: Analysis Of Salt-responsive Transporter Gene Expression On Mmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, RT-PCRs were performed with primers specific for PmSUC2 and for PmUBQ1 (ubiquitin 5 control). Macroarray analyses (data not shown) and PCR analyses (Pommerrenig et al, 2006) had demonstrated that PmUBQ1 expression is not influenced by salt treatment. The data presented in Figure 2A confirmed the salt-responsive induction for PmPLT1 and PmPLT2 expression shown in Figure 1.…”
Section: Analysis Of Salt-responsive Transporter Gene Expression On Mmentioning
confidence: 93%
“…The extracted bundles show a bicollateral phloem anatomy with a central xylem and an abaxial and an adaxial phloem (Gahrtz et al, 1994). Only recently, more than 5,800 ESTs were sequenced from a cDNA library generated from Plantago vascular tissue that had been isolated using this technique (Pommerrenig et al, 2006). Of these sequences, 150 ESTs represented mRNAs of 87 different transporter genes (Pommerrenig et al, 2006).…”
Section: Analysis Of Salt-responsive Transporter Gene Expression On Mmentioning
confidence: 99%
“…The latter shares only limited homology with the three known barley AMY sequences but is highly homologous to a putative rice AMY (GenBank accession no. Os04g0403300) and to a large number of dicot sequences, including those from Plantago major (71.2% identity; Pommerrenig et al, 2006), Malus domestica (70.0% identity; Wegrzyn et al, 2000), and Arabidopsis (68.0% identity; GenBank accession no. At1g76130).…”
Section: Localization Of Starch In the Developing Barley Grainmentioning
confidence: 99%
“…The sterile status of most banana varieties makes it unpractical to establish conventional crossbreeding programmes with elite cultivars, despite the wide diversity of potentially useful traits in the banana germplasm worldwide (Kiggundu et al, 2003b;Heslop-Harrison and Schwarzacher, 2007). By contrast, significant progress has been made in recent years towards the genetic transformation and in vitro regeneration of commercial banana and plantain varieties (Pérez Hernandez et al, 2006;Pommerrenig et al, 2006;Khanna et al, 2007), paving the way to the development of insect- Recombinant cystatins appear of particular interest for the design of pest-resistant transgenic crops intended to human use, given the absence of target cysteine proteases in the human gut and the negligible negative effects expected for these proteins in food products (Arai and Abe, 2000;Atkinson et al 2004b). The potential of midgut cysteine proteases as relevant targets for the control of coleopteran plant pests has also been underlined recently (Tribolium Genome Sequencing Consortium, 2008), considering the diversity of gene coding sequences for cysteine cathepsins in the recently described genome of the coleopteran herbivore Tribolium castaneum (Wang et al, 2007), the widespread occurrence of these enzymes among herbivorous Plant cystatins against the banana weevil Page 5…”
Section: Introductionmentioning
confidence: 99%
“…The sterile status of most banana varieties makes it unpractical to establish conventional crossbreeding programmes with elite cultivars, despite the wide diversity of potentially useful traits in the banana germplasm worldwide (Kiggundu et al, 2003b;Heslop-Harrison and Schwarzacher, 2007). By contrast, significant progress has been made in recent years towards the genetic transformation and in vitro regeneration of commercial banana and plantain varieties (Pérez Hernandez et al, 2006;Pommerrenig et al, 2006;Khanna et al, 2007), paving the way to the development of insectresistant transgenic banana lines. A number of recombinant proteins with pesticidal, antidigestive or antifeedant properties have been identified or devised over the years for the development of herbivorous pest-resistant crops by genetic transformation (Carlini and Grossi-de-Sá, 2002;Christou et al, 2006;Gatehouse, 2008;Zhu-Salzman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%